Christmas in Spain: Religious Syncretism Historical Review - PAVLOVA, ANNA (The journal of contemporary issues in business and government, 2021)
This paper considers the basic features of the festive culture of the Christmas cycle in Spain. It is shown that this series of party actions has born a range of successive layers, incorporating some features of the cultures, which existed on the area of the Iberian peninsula from the time of the Roman sovereignty till nowadays. Based on the factor analysis, four basic factors (the factor of religious syncretism, socio-economic factor, the game factor and the cohesion factor), which modified the picture of the party cycle during the whole period of its existence were derived. As a result of this analysis, the paper concludes that the tradition is being subject to gradual modernization, because of the changes of public discourse.